[OP.8B.09] SODIUM SENSITIVITY AND INVERSE SODIUM SENSITIVITY IN NORMOTENSIVE AND HYPERTENSIVE INDIVIDUALS. (September 2017) - Castiglioni, P.; Parati, G.; Lazzeroni, D.; Bini, M.; Faini, A.; Brambilla, L.; Brambilla, V.; Coruzzi, P.
Abstract : Objective: Traditionally, individuals are dichotomously classified as Sodium Sensitive (SS), if mean blood pressure (BP) is higher after a high-salt than a low-salt diet, or Sodium Resistant (SR) otherwise. Recently, Felder et al. (Curr Opin Nephrol Hypertens, 2013) observed subjects with higher mean BP after the low-salt diet compared with the high-salt diet in a mixed population of normotensives and hypertensives, introducing the class of Inverse Sodium Sensitive (ISS) individuals. Our aim is to compare normotensives and hypertensives following this new classification. Design and method: 71 normotensive (No) volunteers (age 27.4 +5.8 yrs, BMI 22.2 +2.7 kg/m 2, M +SD) and 46 hypertensive (Hy) volunteers (45.0 +7.6 yrs, 24.5 +2.9 kg/m 2 ) underwent high-salt and low-salt diets (30 vs. 200 mmol NaCl/day), each of 5-day duration. Brachial BP was measured at the end of each diet and the Sodium Sensitivity Index (SS-Index) calculated as ratio between difference in mean BP and difference in 24-hour urinary sodium excretion rate. We classified participants as ISS if SSIndex was <−15 mmHg/(mol × day), as SS if SS-Index was > 15, as SR otherwise. We compared differences between high- and low-salt diets in Systolic BP (SBP), Diastolic BP (DBP) and Heart Rate (HR) by ANOVA. Results: The 3 classes were homogeneously distributed in the No group (ISS = 41%; SR = 35%; SS = 24%) while SS individuals prevailed in the Hy group (ISS = 7%; SR = 22%; SS = 72%, p < 0.01 comparing No with Hy by Chi-square test). The figure shows m+sem of the difference between high- and low-salt diets (δ) stratified by class of sodium sensitivity. Hy and No groups had the same trend for DBP (factors significance: class p < 0.01; group p = 0.92; interaction p = 0.40). This was not the case for SBP (class p < 0.01; group p < 0.01; interaction p = 0.05), with greater SBP increase in SS individuals of Hy group. The high-salt diet decreased HR without significant differences among classes or between groups (class p = 0.08; group p = 0.34; interaction p = 0.76). Figure. No caption available. Conclusions: ISS individuals are common among normotensives and rare among hypertensives. SS hypertensives have greater pressor response to salt than SS normotensive but for Systolic BP only, not for Diastolic BP.